2010
DOI: 10.1136/oem.2010.058156
|View full text |Cite
|
Sign up to set email alerts
|

Saharan dust and daily mortality in Emilia-Romagna (Italy)

Abstract: Objective To investigate the association between Saharan dust outbreaks and natural, cardiovascular and respiratory mortality. Methods A caseecrossover design was adopted to assess the effects of Saharan dust days (SDD) on mortality in the Emilia-Romagna region of Italy. The population under study consisted of residents in the six main towns of the central-western part of the region who died between August 2002 and December 2006. The association of Saharan dust outbreaks and PM 10 concentration with mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 41 publications
6
51
0
Order By: Relevance
“…Three studies reporting the negative relationship for respiratory mortality are the same as those reporting the total mortality [19,20,22]. An exceptional study reported positive relationship for respiratory mortality but negative relationship for total mortality in Athens [21].…”
Section: Mortality Effects From Desert Dust Coarse Particles Pm 10 Amentioning
confidence: 94%
See 2 more Smart Citations
“…Three studies reporting the negative relationship for respiratory mortality are the same as those reporting the total mortality [19,20,22]. An exceptional study reported positive relationship for respiratory mortality but negative relationship for total mortality in Athens [21].…”
Section: Mortality Effects From Desert Dust Coarse Particles Pm 10 Amentioning
confidence: 94%
“…In general, long-distance transport reduces the number of heavier and larger particles in Saharan air masses, thus increasing the relative contribution of smaller particles. The results show that PM 2.5-10 (the usual definition of the coarse fraction adopted in air pollution monitoring and in epidemiological studies) should be employed with caution as a specific marker of Saharan dust transport, which is probably better described by PM 1-10 [22,67].…”
Section: Mortality Effects Of Desert Dustmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies showed that dust originating from the Sahara is mainly transported to the Caribbean and South America [2,3], the Mediterranean and Europe [4], the eastern Mediterranean (EM hereafter), and the Middle East [5]. Due to the transfer of the Saharan dust to distant places of the world, numerous studies investigated its impacts on health problems (e.g., [6][7][8][9][10][11]), atmospheric heating and stability [12], cloud formation and radiation [13], and visibility [14], from regional perspectives. In the EM basin (extending from Turkey to northern Africa and eastward to Iran), dust loadings originating from Sahara are shown mostly in spring months [15] due to the occurrence of intense Sharav cyclones, which are generated by the thermal contrast between cold Atlantic air and warm continental air, over the south of the Atlas Mountains (Morocco).…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind that African dust is an important source of particulate matter pollution in specific areas, causing by itself or contributing to exceed the daily limit values of PM 10 (in Europe being established in 50 µg m −3 by the 2008/50/EC Directive), and exerting negative health outcomes (Middleton et al, 2008;Mitsakou et al, 2008;Pérez et al, 2008;Jiménez et al, 2010;Mallone et al, 2011;Zauli Sajani et Samoli et al, 2011a, b;Tobías et al, 2011a, b), the identification of such episodes and the quantification of daily and annual contributions of desert dust to PM is currently necessary. Moreover, the identification of temporal trends in African dust contributions at ground-based monitoring sites may be indicative of atmospheric circulation changes.…”
Section: Introductionmentioning
confidence: 99%